Asymptomatic presentation of Vallecular Cyst in an Adult - Biswas, Binoy Krishna; Khan, Manjurul Karim; Ansari, Nasma Parvin; Khan, Md Abul Kalam Azad; Hasan, Rajibul (Community Based Medical Journal, 2013)
DOI: http://dx.doi.org/10.3329/cbmj.v1i2.13865 Community Based Medical Journal Vol.1(2) 2012 56-58